Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2196/21613
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for Social Distancing and App Use as Complementary Measures to Combat the COVID-19 Pandemic: Quantitative Survey Study

Abstract: Background The current COVID-19 pandemic is showing negative effects on human health as well as on social and economic life. It is a critical and challenging task to revive public life while minimizing the risk of infection. Reducing interactions between people by social distancing is an effective and prevalent measure to reduce the risk of infection and spread of the virus within a community. Current developments in several countries show that this measure can be technologically accompanied by mob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
134
4
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(161 citation statements)
references
References 48 publications
17
134
4
6
Order By: Relevance
“…Our findings corroborate prior research suggesting that the perceived severity of COVID-19, not the perceived vulnerability, had a positive impact on the social isolation intention (Callow, Callow, & Smith, 2020;Farooq, Laato, & Islam, 2020;Kaspar, 2020). It suggests that intervention strategies motivating people to socially isolate during the COVID-19 pandemic should focus on stressing the severity of the COVID-19 but not on emphasizing that everybody is vulnerable to the disease, which can be a useful recommendation for frontline practitioners.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings corroborate prior research suggesting that the perceived severity of COVID-19, not the perceived vulnerability, had a positive impact on the social isolation intention (Callow, Callow, & Smith, 2020;Farooq, Laato, & Islam, 2020;Kaspar, 2020). It suggests that intervention strategies motivating people to socially isolate during the COVID-19 pandemic should focus on stressing the severity of the COVID-19 but not on emphasizing that everybody is vulnerable to the disease, which can be a useful recommendation for frontline practitioners.…”
Section: Resultssupporting
confidence: 90%
“…Some recent studies confirmed that perceived vulnerability is a significant predictor of engaging in proactive and social distancing behaviours during the COVID-19 pandemic (Makhanova , & Shepherd, 2020;van Rooij et al, 2020). However, other studies demonstrated that the perceived severity of COVID-19, not the perceived vulnerability, had a positive impact on social isolation intention (Callow, Callow, & Smith, 2020;Farooq, Laato, & Islam, 2020;Kaspar, 2020). Different studies demonstrated that neither perceived severity nor perceived vulnerability to COVID-19 was a significant predictor of health-related behaviours during the COVID-19 pandemic (Clark, Davila, Regis, & Kraus, 2020).…”
Section: Perceived Vulnerability and Severity Of Covid-19mentioning
confidence: 99%
“…Our findings corroborate prior research suggesting that the perceived severity of COVID-19, not the perceived vulnerability, had a positive impact on the social isolation intention (Callow, Callow, & Smith, 2020;Farooq et al, 2020;Kaspar, 2020). It suggests that intervention strategies motivating people to socially isolate during the COVID-19 pandemic should focus on stressing the severity of COVID-19 but not on emphasizing that everybody is vulnerable to the disease, which can be a useful recommendation for frontline practitioners.…”
Section: Discussionsupporting
confidence: 86%
“…Some recent studies confirmed that perceived vulnerability is a significant predictor of engaging in proactive and social distancing behaviours during the COVID-19 pandemic (Makhanova & Shepherd, 2020;van Rooij et al, 2020). However, other studies demonstrated that the perceived severity of COVID-19, not the perceived vulnerability, had a positive impact on social isolation intention (Callow et al, 2020;Farooq et al, 2020;Kaspar, 2020). Different studies demonstrated that neither perceived severity nor perceived vulnerability to COVID-19 was a significant predictor of health-related behaviours during the COVID-19 pandemic (Clark et al, 2020).…”
Section: Perceived Vulnerability and Severity Of Covid-19mentioning
confidence: 99%
“…Following the rapid spread of the virus, nearly all countries have introduced temporary restrictions affecting daily life, with “social distancing” as a key intervention for slowing the spread of the virus [ 5 ]. Besides these strategies, many companies have introduced or expanded home office–based work, which lead to a tremendous increase in the use of video web conference platforms such as Skype for Business (Microsoft Corporation), Zoom (Zoom Video Communications), Google Hangouts (Google LLC), Adobe Connect (Adobe Systems), or GoToMeeting (LogMeIn).…”
mentioning
confidence: 99%